Real-World Cost-Effectiveness Analysis of Gemcitabine and Cisplatin Compared to Docetaxel and Cisplatin Plus Fluorouracil Induction Chemotherapy in Locoregionally Advanced Nasopharyngeal Carcinoma - Yang, Jiangping; Han, Jiaqi; He, Jinlan; Duan, Baofeng; Gou, Qiheng; Ai, Ping; Liu, Lei; Li, Yanchu; Ren, Kexing; Wang, Feng; Yao, Min; Chen, Nianyong (Frontiers in Oncology, 2020)
Background: Addition of gemcitabine and cisplatin (GP) or docetaxel and cisplatin plus fluorouracil (TPF) to concurrent chemoradiotherapy (CCRT) signiﬁcantly improved survival in locoregionally advanced nasopharyngeal carcinoma (NPC). However, an economic evaluation of these regimens remains unknown. The purpose of this study is to compare the cost-effectiveness of GP versus TPF regimen in the treatment of locoregionally advanced NPC in China. Materials and methods: A comprehensive Markov model was developed to evaluate the health and economic outcomes of GP versus TPF regimen for patients with locoregionally advanced NPC. Baseline and clinical outcome were derived from 158 patients with newly diagnosed stage III-IVA NPC between 2010 and 2015. We evaluated the quality-adjusted life-years (QALYs), costs, and incremental cost-effectiveness ratios (ICERs) from the perspective of the Chinese healthcare system. One-way sensitive analysis explored the impact of uncertainty in key model parameters on results, and probabilistic uncertainty was assessed through a Monte Carlo probabilistic sensitivity analysis. Results: GP regimen provided an additional 0.42 QALYs with incremental cost of $3,848.61, resulting in an ICER of $9,099.98 per QALY versus TPF regimen at the real-world setting. One-way sensitivity analysis found that the results were most sensitive to the cost and proportion of receiving subsequent treatment in two groups. The probability that GP regimen being cost-effective compared with TPF regimen was 86.9% at a willingness-to-pay (WTP) of $31,008.16 per QALY. Conclusion: Using real-world data, GP regimen was demonstrated a cost-effective alternative to TFP regimen for patients with locoregionally advanced NPC in China. It provides valuable evidence for clinicians when making treatment decisions to improve the cost-effectiveness of treatment.